Linearized correction to a flamelet-based model for hydrogen-fueled supersonic combustion. (20th April 2017) - Shan, Fanli; Hou, Lingyun; Chen, Zheng; Chen, Jun; Wang, Ling
Abstract: To account for compressibility effects on chemistry in supersonic combustion, a new linearized correction applied to a flamelet-based model incorporating a progress variable is proposed. The basis of this correction is a Taylor series expansion for the source term of the progress variable equation, along with a theoretical derivation of the partial derivatives in the expansion. This avoids a case-by-case preprocessing step before the actual simulation and therefore allows the correction to be applied to various scenarios. Using this correction, hydrogen-fueled supersonic combustion is simulated and superior predictions for temperature distributions are generated. This correction determines the deviation in the chemical reaction progress rate from compressibility effects and is capable of correcting the chemical reaction progress rate based on local conditions. Taking this effect into account improves the accuracy of predictions for local reaction rates and thereby generates a reasonable characterization of compressibility effects on chemical reaction progress and reaction pathway. Highlights: A linearized compressibility correction to the FPV model is originally proposed. The correction is theoretically formulated and thus case independent. The correction improves predictions for supersonic combustion characteristics. The correction promotes characterizing compressibility effects on chemistry.